A 3D Model of Human Trabecular Meshwork for the Research Study of Glaucoma - Tirendi, Sara; Saccà, Sergio Claudio; Vernazza, Stefania; Traverso, Carlo; Bassi, Anna Maria; Izzotti, Alberto (Frontiers in Neurology, 2020)
Glaucoma is a multi-factorial syndrome in which the development of pro-apoptotic signals are the causes for the retinal ganglion cells (RGC) loss. Most of research progresses in the glaucoma field have been based on animal models which, however, provided only for some molecular aspects of glaucoma process. In fact, up today all glaucoma molecular mechanisms have not yet been identified maybe due to the animal model choice to mimic this disease. Rodents and other small animals are the most widely used both for ethical and economical reasons. However, the low degree of similarity with human eye anatomy, the lack of age-related damage and the poor standardization of experimental procedure for intraocular pressure elevation, represent the main disadvantages that compromise the full understanding of adverse outcomes underlying glaucoma cascade. In this regard, according to at least two of the 3Rs’s principles, there is a need for reliable human-based in vitro models to better clarify the mechanisms involved in disease progression, replacing or reducing the animal experiments. The proper selection of an in vitro model with a “closer to in vivo” microenvironment and structure, for instance, allow identifying those biomarkers involved in early stages of glaucoma and then develop also new therapeutic approaches. This review summarizes the most recent findings in glaucoma field by the use of both human two-and three dimensional cultures. In particular it focuses on the role of the scaffold and the use of bioreactors in preserving the physiological relevance of in-vivo condition of the human trabecular meshwork cells in three dimensional cultures. Moreover, data from these studies highlight also the pivotal role of oxidative stress in promoting trabecular meshwork pro-apoptotic signals which are the first stages of trabecular meshwork damage leading to loss of the barrier function and intraocular pressure increase as well promoting neuroinflammation and many other cell degenerations causing glaucoma. Therefore, a better understanding understanding of the first molecular events which drive glaucoma cascade allows identifying new targets for an early neuroprotective therapy.